MAKING METHODS AGE FRIENDLY: METHODS, MOVEMENT, AND MAPPING. (11th November 2018) - Lawthom, R; Woolrych, R; Fisher, J; Murray, M; Smith, H; Garcia-Ferrari, S; Portella, A; Pereira, G
Abstract: Researching age- friendly communities, which meet the needs of older people, requires methods which are sensitive to place and age. Working across countries and sensitive to neighbourhood context, culture, and older people as expert knowers, we developed a range of methods used to explore the concept of sense of place. These ranged from individual mobile explorations of neighbourhoods, interviews and surveys. Within each neighbourhood with older people, participatory mapping allowed an interactive, asset-based approach, which recognised residents as experts. The creation of maps that articulate experiential and spatial knowledge to others, allowed us to utilise the World Café approach to involve other stakeholders. We present reflections on the methodology. This paper will be of interest to academics, policy makers and practitioners in terms of developing creative methods aimed at understanding the experiences of older adults as a means to designing age-friendly supports and services.